Cross-Cultural Consumer Acceptability for Ethnic Fermented Sauce Products: Comparisons among Korean, UAE, and US Consumers - Kim, Mi-Ran (Foods, 2020)
The present study investigated the drivers of liking ethnic sauces in a cross-cultural context. Experiments were conducted to understand the acceptance of salad dressings and dipping sauces developed from Korean fermented seasonings among consumers with different ethnic backgrounds, including: South Korean, United Arab Emirates (UAE), and American. The samples of interest included four types of salad dressings made from fermented soybean paste (doenjang) and four types of spicy dipping sauces made from fermented chili pepper paste (gochujang). The salad dressings were preferred by Korean and US consumers. Koreans liked the nutty-flavored salad dressings, whereas UAE and American consumers commonly liked the spicy type. There was a stronger cross-cultural agreement in liking dipping sauces rather than salad dressings. Both Korean and American consumers liked spicy dipping sauces that elicited a sweet taste. UAE consumers tended to prefer the less spicy dipping sauce samples. Consumers in all three countries generally liked spicy dipping sauces more than salad dressings. Cultural differences were observed between the responses depending on the presence and level of spiciness in the two different food types. For product development with ethnic fermented flavors or chili spices, the contextual appropriateness and consumer familiarity with the corresponding flavor should be taken into account.